Framework especialista de ferramentas para avaliação ergonômica - Laperuta, Dalila Giovana Pagnoncelli (2016)
To propose a specialist in ergonomics and ergonomic assessment methods/tools interface, this study searched to know and analyze the investigated scenario and propose solutions. This study begins in the investigation of these methods, defining them, quantifying the related publications and contrasting this information with the methods used by professionals, their insights and recommendations. These prospects took the authors to investigate the process of ergonomic analysis, from the literature and field procedures, in order to propose a software that would help the process of choosing and applying the methods. Software engineering supports a survey of requirements to identify the needs of local experts in Pato Branco - PR. These requirements were ranked and mapped in software prototype, validated by professionals. From these analyzes (process and requirements), a conceptual framework has been proposed to represent a new approach to the process where the assessment is carried out from the evaluable aspect, it is possible to apply all related methods that are incorporated into the software. This new approach does not replace the previous one, however, dispenses the choice without exclude it, allowing the expert to know, apply and analyze the results of different methods, regardless of their professional portfolio. The initial version of the prototype was developed and a pilot test was applied to an ergonomics company, for software validation. The software application results enriched the current approach, allowing the application of a method that did not belong to the professional portfolio, reinforcing previous evaluations and bringing new contributions to the ergonomic evaluation.